Efeito neuroprotetor da Berberina na neurotoxicidade induzida por estreptozotocina e lipolissacarídeo em ratos - Oliveira, Juliana Sorraila de (2019)
Alzheimer's disease (AD) is considered the major cause of dementia and is characterized by changes in the cholinergic and purinergic system, oxidative stress, inflammatory process and metabolic changes that, in turn, are responsible for brain cell death with consequent memory loss and other significant symptoms. On the other hand, Berberine (BRB), an alkaloid widely used in traditional Chinese medicine has had significant effects on neurodegenerative diseases, including AD. The benefits described by the use of BRB concern, among others, its antioxidant, anti-inflammatory and neuroprotective ability. Thus, the aim of the present study was to investigate the effects of BRB on memory and to relate these changes with the cholinergic system, purinergic system and oxidative stress through two experimental rat models widely used in the investigation of AD candidate compounds. Therefore, the first investigation was through the study of BRB at doses of 50 and 100 mg/kg on the model of dementia induced by intracerebroventricular injection of streptozotocin (ICV-STZ). The rats were submitted to ICV-STZ 3 mg/kg or saline solution and, 3 days later, BRB treatments at 50 or 100 mg/kg or saline for 21 days were started. Behavioral assessment of memory as well as oxidative stress parameters and activity of ectoenzymes in samples of cerebral cortex and hippocampus were investigated.. The results demonstrated that BRB at both doses was effective in protecting against memory impairment, oxidative stress and decreased activity of the enzymes NTPDase, 5'-Nucleotidase and adenosine deaminase. The second study concerns the analysis of BRB on the experimental model of lipopolysaccharide-induced neuroinflammation (LPS). The animals were submitted for 8 consecutive days to an injection (ip) per day of LPS at a dose of 250 μg / kg body weight and BRB at a dose of 50 mg/kg was administered orally 30 minutes after LPS for 8 days. BRB has been shown to be effective in protecting recognition memory, increased acetylcholinesterase activity, oxidative stress and decreased NTPDase and 5'-nucleotidase ectoenzyme activity in cerebral cortex and hippocampus samples from LPS animals. Taken together, we can suggest that BRB has a potent antioxidant activity on Alzheimer's dementia with the potential to modulate cholinergic and purinergic system pathways. In this context, the use of BRB can be pointed as a new therapeutic and multi-target strategy to be considered in the treatment of AD.